Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Grain Sorghum - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2016)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated grain sorghum in western Kansas. In 2015, N applied alone increased yields 66 bu/a, whereas N and P applied together increased yields up to 92 bu/a. Averaged across the past 10 years, N and P fertilization increased sorghum yields up to 76 bu/a. Application of 40 lb/a N (with P) was sufficient to produce 88% of maximum yield in 2015 which is slightly above the 10-year average. Application of potassium (K) has had no effect on sorghum yield throughout the study period. Average grain N content reached a maximum of ~0.7 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu) and grain K content reached a maximum of 0.19 lb/bu (0.23 lb K2O/bu).
Keywords: Nitrogen fertilization; phosphorus fertilization; irrigated grain sorghum; long-term fertility; nutrient removal